Activation of T cells by dendritic cells exposed to a reference sensitizer: Towards a promising model to assess the allergenic potential of chemicals. (10th April 2018) - Huppert, Cécile; Paris, Christophe; Langonné, Isabelle; Muller, Samuel; Mathiot, Julianne; Abdessadeq, Hakima; Gagnaire, François; Battais, Fabrice; Sponne, Isabelle
Abstract : Background: Low molecular weight chemicals constitute one of the major causes of occupational allergies. European legislation on chemicals recommends limiting the use of in vivo models for assessing the sensitizing potential of chemicals, and encourages the development of integrated alternative methods. An in vitro mouse model of bone marrow‐derived dendritic cells (BMDCs) that showed good accuracy (75%) and sensitivity (69%) has previously been developed to assess the sensitizing potential of chemicals. Objective: To assess the ability of BMDCs to activate T cells (TCs) in vitro. Methods: BMDCs pre‐exposed to the reference sensitizer ammonium hexachloroplatinate (AHCP) were co‐cultured with different subpopulations of TCs. TC activation was assessed by surface marker expression, proliferation, and cytokine release. Results: The results showed significant activation of TCs co‐cultured with dendritic cells pre‐exposed to AHCP as evaluated by CD124 expression, proliferation, and cytokine secretion. Moreover, the response of TCs appeared to be Th2‐oriented. Naive TCs were shown to be involved in this response, and the removal of regulatory TCs did not improve the cell response. Conclusions: The BMDCs used in this previously developed model appear to have the ability to activate TCs, confirming that the BMDC model represents a reliable assay for assessing the sensitizing potential of chemicals.